Keragaman Karakter Morfologi, Komponen Hasil, dan Hasil Plasma Nutfah Kedelai (Glycine max L.) - Putri, Priskilla Purnaning; Adisyahputra, Adisyahputra; Asadi, Asadi (LPPM Universitas Negeri Jakarta, 2014)
Abstract Soybean (Glycine max L.) is annual crop that have high morphologies and yield components diversity. The research was conducted at the first season of 2011, the objective of the research were to find morphological, yield, and yield component of Soybean germplasm (Glicine max L.). The research was carried out at experimental station BB-BIOGEN Citayam, Depok, and laboratory of Gene Bank BB-BIOGEN. The experiment used randomized block design with 100 different accessions and three replications for each accession. Based on the observation, the morphological characters have many visual forms. They are as follows: growth percentage in which 19.33 – 99%; growth types were determinate and indeterminate, the leave form was triangle to sharp; purple and white flowers; yellow and black seeds color. The range of values for each characteristic component are as follows: plant height 29,23 – 104,25 cm; number of pods per plant was 23,6 – 99,82; flowering time 33 – 47 days after planting; 100 seed weight 5,98 – 20,77 gram; maturing time 75 – 96,67 days after planting; root nodule’s weight 0,004 – 0,109 gram; seed’s weight 3,15 – 11,45 gram/plant. Among the accessions, the highest yield was shown by B 4323 (643,27 gram/3,6 m2). Significant correlation was shown between soybean’s yield components and yield which were plant’s height, growth percentage, numbers of main stem’s node, numbers of pods, seeds weight for each plant and root nodule’s weight. 100 seeds weight showed significant negative correlation with soybean components. Key words: germplasm, morphological characteristics, soybean, yield components